Pandangan Al-Qur’an Terhadap Hoaks Persepektif Tafsir Maqāṣidī (Studi Q.S. Al-Ḥujurāt: 6 dan al-Nūr: 15) - Siti Nur Istiqomah; Muhammad Nur Amin; Muhammad Ikhwanudin (Kuras Institute, 2025)
The phenomenon of hoax dissemination in the digital era has become a serious challenge with far-reaching impacts on social stability, political dynamics, and religious life among Muslim communities. The Qur’an, as the holy scripture of Islam, offers fundamental principles for responding to information, particularly through verses that emphasize verification and caution, such as Q.S. al-Ḥujurāt [49]:6 and Q.S. al-Nūr [24]:15. This study aims to analyze the content of these two verses using the maqāṣidī tafsir approach as developed by Abdul Mustaqim, in order to uncover the substantial and contextual values of Islamic law. This research employs a qualitative method with a descriptive-analytical approach based on literature review from primary and secondary authoritative tafsir sources. The findings reveal that these verses encompass core values of maqāṣid al-sharī‘ah, including: ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-dīn (protection of religion), ḥifẓ al-dawlah (protection of the state), and ḥurriyyah al-mas’ūliyyah (responsible freedom). These values are not only normative but also practical in addressing the challenges of modern disinformation. Thus, the maqāṣidī approach presents a relevant and solution-oriented methodology for shaping ethical media engagement and fostering responsible Islamic digital literacy in contemporary society.